2013
DOI: 10.1038/nmeth.2397
|View full text |Cite
|
Sign up to set email alerts
|

A Y2H-seq approach defines the human protein methyltransferase interactome

Abstract: A 'writer-reader-eraser' post-translational modification regulatory system consisting of a large number of methyltransferases 8,9 , methyl-recognition domain-containing proteins 10 and putative demethylases 11 are expressed in different subcellular locations in humans, an indication that protein methylation is involved in processes other than epigenetic regulation.We prepared 82 Y2H bait strains spanning human R-methyltransferases (PRMT1-PRMT8) 8 , 16 SET domaincontaining K-methyltransferases (PKMTs) 9 , 9 mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
97
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 25 publications
9
97
0
Order By: Relevance
“…Moreover, as previous studies in our laboratory demonstrated that QKI-5 mediates the response of liver tumoral cells to a therapeutic oncolytic vector (31), we wonder whether its methylation could be a mechanism to regulate its activity. Two QKI-5 methyl peptides were identified, containing R242, in agreement with previous reports (53), and R242 and 256 (Fig. 5A).…”
Section: Mta Increases the Proliferation Rate Of Sk-hep1supporting
confidence: 91%
“…Moreover, as previous studies in our laboratory demonstrated that QKI-5 mediates the response of liver tumoral cells to a therapeutic oncolytic vector (31), we wonder whether its methylation could be a mechanism to regulate its activity. Two QKI-5 methyl peptides were identified, containing R242, in agreement with previous reports (53), and R242 and 256 (Fig. 5A).…”
Section: Mta Increases the Proliferation Rate Of Sk-hep1supporting
confidence: 91%
“…Interestingly, recombinant PRMT2 enhanced the activity of recombinant PRMT1 up to 15-fold even when PRMT2 harbored inactivating mutations, suggesting a possible regulatory role for PRMT2. Human PRMT3 was first identified in a yeast two-hybrid screen using PRMT1 as bait (29), and the interaction of human PRMT1 and PRMT8 has been documented by several high throughput studies and directed experiments (61)(62)(63)(64). In Arabidopsis, two CARM1 (PRMT4) homologs interact in vitro and in vivo, although homodimeric CARM1 complexes are also present (65).…”
Section: Promentioning
confidence: 99%
“…hsPrp38 is a major PPI hub in the spliceosome High-throughput approaches, such as affinity purification coupled to mass spectrometry and Y2H assays, have been used to map PPIs in multiprotein complexes , specific cellular processes (Weimann et al 2013), or even entire proteomes (Woodsmith and Stelzl 2014). The deduced interaction networks show that the majority of the involved proteins interact with one or a few partners, whereas a limited set of hub proteins exhibit many interactions (Barabási and Oltvai 2004).…”
Section: Functional Architecture Of Human Prp38mentioning
confidence: 99%